Women With Clinically Significant Fatigue After Breast Cancer Treatment Report Increased Falls and Perform Poorly on Objective Measures of Physical Fitness and Function. Issue 2 (April 2020) - Wood, Lisa J.; Winters-Stone, Kerri M.; Kneiss, Janet A.; Fox, Annie B.; Walker, Rachel K.
Abstract : Purpose: To determine whether there were significant differences in self-report and objective measures of physical fitness and function between women post–breast cancer (BC) treatment with and without clinically significant fatigue. Methods: We performed a secondary analysis of baseline data collected from 281 postmenopausal women post–BC treatment (62 ± 10 years; time since diagnosis = 5.6 ± 3.9 years) who participated in prior exercise trials. Scores on the SF-36 (36-Item Short Form Health Survey) vitality subscale (0-100) were used to identify women with clinically significant fatigue, where a score of 45 or less represents fatigue and a score of 70 or more represents no fatigue. Objectively measured function included maximal leg press strength (kg), physical function battery, timed chair stand, Unipedal Stance Test, and gait characteristics. Self-reported outcomes included physical function, pain, mental health, sensory symptoms of chemotherapy-induced peripheral neuropathy (CIPN), habitual physical activity level, and fall history. Results: Twenty percent of women (n = 57) reported clinically significant fatigue 6 years postdiagnosis, whereas 34% (n = 100) reported no fatigue. Except for leg strength, unipedal stance, step length, and base of support while walking, fatigued women had significantly worse objectively measured function than women without fatigue. Fatigued women also reported poorer physical function, greater bodily pain, and poorer mental health and were twice as likely as nonfatigued women to report symptoms of CIPN and having fallen. Conclusions: Women with a history of BC, and in particular those with CIPN, should be routinely screened for clinically significant fatigue in the survivorship period. Clinical and survivorship care plans aimed at limiting functional decline and reducing falls in survivors of BC should include fatigue-reduction strategies.